A broadband compact filtering antenna for sub‐6 GHz base station applications. Issue 12 (24th September 2022) - Zhang, Yifan; Jia, Yuxin; Sun, Yu; Zhai, Huiqing; Liu, Changyuan
Abstract: A compacted dual‐polarized base station antenna with filtering characteristics and enhanced broadband is proposed for sub‐6 GHz applications in this letter. The lower stopband radiation null is thus generated by the parasitic loops on the back of the substrate. In order to achieve the filtering response and extend the bandwidth of at the upper edge of the passband, a split strip‐type dipole arm is added to the inner part of the annular dipole to form the radiation null. On the flip side, by changing the shape of the Balun ground, another filtering null is generated at the upper‐band to suppress the second harmonic, achieving better broadband suppression performance. The experimental results show that the antenna has a 42.9% (3.3–5.1 GHz) impedance bandwidth, and the in‐band average gain reaches 8.3 dBi, while the out‐of‐band gain suppression is greater than 17 dB.